The Influence of Shopping Motivation On Sustainable Consumption: A Study Related To Eco-Friendly Apparel (Journal of Social Sciences Review, 2023)
The influence of consumers' intentions to purchase eco-friendly clothing is examined, with the moderating effect of consumption value. Also examined were reasons for the disparity between consumer purchase intention and buying behavior regarding green apparel. A questionnaire on a five-point Likert scale was utilized to collect data. One hundred ninety-seven responses were found valid out of 384 for analysis. Smart PLS and SPSS were used to analyze the data. By the analysis found a significant impact of hedonic motivation and utilitarian motivation on green purchase intention with moderating impact on consumption value for the purchase behavior of the consumer. Gender and income were also found to have a controlling impact on the Hedonic and utilitarian motivation of consumers. The impact of consumer information availability, convenience to buy, and customized offerings of green textile brands for consumers’ motivation to buy. Also, consumer beliefs related to environmental issues, social and trends significantly impact the motivation of consumers to purchase green apparel. The study of post-purchase behavior based on consumption value has been a new concept that is added in this research paper on an existing study. The research will be useful to manufacturers in understanding how consumers will buy green clothing in a sustainable way that benefits both the environment and consumers.
Keywords: Green Apparel; Utilitarian Motivation; Hedonic Motivation; Green Purchase Intention; Consumption Value; , Green Purchase Behavior